2016
DOI: 10.1080/15568318.2016.1191094
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of residential dissonance: Implications for transit-oriented development in Brisbane

Abstract: Residential dissonance is the mismatch of land use patterns between individuals' actual and preferred neighbourhood type. It is a threat to land use based policy interventions, such as transit oriented development (TOD), aiming to enhance sustainable mobility behaviour. Dissonants in TOD are more likely to use the car and less likely to use public transport. They do not naturally adjust their preferences according to their surrounding land use patterns and continue their predisposition travel behaviour. Theref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 71 publications
1
17
0
Order By: Relevance
“…Comparing the estimated shares of monthly walking distance, respondents living in the areas with the highest observed walkability walked all in all more than those living in lowwalkable areas, whereas respondents preferring high-walkable neighborhoods walked more than those preferring low-walkable neighborhoods. These results are generally in line with observations from earlier dissonance studies with no differentiation between active travel modes (Badland et al 2012;Kamruzzaman et al 2013Kamruzzaman et al , 2016aSchwanen and Mokhtarian 2005b). Results of the ordinal logistic regression analyses confirmed that low-walkability consonants had the lowest and high-walkability consonants the highest adjusted odds of walking a high share of their estimated number of monthly trips and travel distance.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Comparing the estimated shares of monthly walking distance, respondents living in the areas with the highest observed walkability walked all in all more than those living in lowwalkable areas, whereas respondents preferring high-walkable neighborhoods walked more than those preferring low-walkable neighborhoods. These results are generally in line with observations from earlier dissonance studies with no differentiation between active travel modes (Badland et al 2012;Kamruzzaman et al 2013Kamruzzaman et al , 2016aSchwanen and Mokhtarian 2005b). Results of the ordinal logistic regression analyses confirmed that low-walkability consonants had the lowest and high-walkability consonants the highest adjusted odds of walking a high share of their estimated number of monthly trips and travel distance.…”
Section: Discussionsupporting
confidence: 90%
“…Findings from non-walking-specific residential dissonance studies in the US and Australia suggest that in both urban and suburban settings, residents preferring high-walkable or transport-oriented residential environments are more likely to engage in active travel than residents with preference for car-oriented environments (Badland et al 2012;Kamruzzaman et al 2013Kamruzzaman et al , 2016aSchwanen and Mokhtarian 2005b). De Vos et al (2012) reported similar results in Flanders, Belgium, observing that urban consonants were the most frequent users of active transportation modes while travelling to leisure destinations, followed by rural dissonants, urban dissonants, and rural consonants.…”
Section: Residential Dissonance and Walkingmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, the models also indicate that there is large variation in people’s preferences: people with stronger preferences towards active travel are more likely to move into more liveable neighbourhoods, if they can afford to do so. Indeed, previous studies have suggested a latent demand for more walkable communities, with the majority of people living in low walkable environments preferring instead to live in areas where they could walk to local amenities [52, 53]. However, other factors influence people’s choice of neighbourhoods, with the most important factors being housing affordability [54].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, there is mounting evidence that people increasingly seek to live in more compact cities. Recent surveys find that a growing number of people prefer denser living environments over a detached house and yard (Newton et al 2017) and that most baby boomers want to live in a dense and walkable neighbourhood (Kamruzzaman et al 2016). Advocates argue that new density proposals respond to this latent market demand while producing more sustainable urban environments.…”
Section: Compact City Promise and Realitiesmentioning
confidence: 99%